CYTOTOXIC EFFECT OF ASPARAGINASE PRODUCE FROM E.COLI AND CONJUGATED WITH ZNO NANOPARTICLES ON CANCER CELL LINES - Zahraa H. H.; H. A. Rasheed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to examine the anticancer activity of fabricated ZnONPs- L-ASNase conjugate against cancer and normal cell lines. Total of 127 bacterial isolates were taken from clinicalandenvironmentalsamples then identified as E.coli.In this work, 88 isolates were identified as E.coli.L-asparaginase produced from E.coli were screened¸clinical Isolates of E.coli from urine sample have the potential to produce asparaginase that is responsible for cytotoxicity¸the optimal culture conditions for the development of the enzyme L-asparaginase were determined to be 37ºC and pH8. Nitrogen sourceconcentrations at 0.9gm/ml were discovered to maximize enzyme production. L-asparaginase then purified by two steps that includeion exchange column and gel filtration. Purification and recovery percentage for L-ASNase was 6.21%, 10.34% respectively. Effective conjugation was approved by UV-visible spectroscopy. ZnO nanoparticles exhibit absorbance peaks approximately 200-300 nm. XRD analysis confirmed the crystallite size of the ZnO nanoparticles was observed to be 18.4 nm. The activity of L-ASNase in the ZnONPs-L-ASNasewas detected by a direct nesslerization method and the findings showed a substantial increase L-ASNase specific activity within the conjugate of ZnONPs-L-ASNase in comparison to its free state. The ZnONPs-L-ASNase conjugate showed the greatest and most substantial cytotoxic action against A375 with survival rate at 400 µg /mL about 45.8± 2.3. The IC50 value of 44.69 µg/ mL of ZnONPs- L-ASNase was calculated for A375 cells. In comparison, all substances exhibited weak to moderate cytotoxicity when tested against the normal cell line WRL-68. The ZnONPs-L-ASNase combination therapy resulted in a higher cytotoxic effect. This action could be attributed to the synergetic effects of both L-ASNase and the conjugated molecules ZnONPs.